**Solving the Equation: 7y - 6(0.2y - 1) = 5(y + 2) - 1**

In this article, we will solve the equation 7y - 6(0.2y - 1) = 5(y + 2) - 1 step by step.

**Step 1: Simplify the Left Side of the Equation**

Let's start by simplifying the left side of the equation:

7y - 6(0.2y - 1)

= 7y - 6(0.2y) + 6(1)

= 7y - 1.2y + 6

= 5.8y + 6

**Step 2: Simplify the Right Side of the Equation**

Now, let's simplify the right side of the equation:

5(y + 2) - 1

= 5y + 10 - 1

= 5y + 9

**Step 3: Equate the Two Expressions**

Now that we have simplified both sides of the equation, we can equate them:

5.8y + 6 = 5y + 9

**Step 4: Solve for y**

To solve for y, we can subtract 5y from both sides of the equation:

0.8y + 6 = 9

Subtracting 6 from both sides gives us:

0.8y = 3

Dividing both sides by 0.8 gives us:

y = 3/0.8

y = 3.75

Therefore, the value of y is **3.75**.

**Conclusion**

In this article, we have successfully solved the equation 7y - 6(0.2y - 1) = 5(y + 2) - 1. The value of y is 3.75.